Answer:
x = 4
Step-by-step explanation:
Simplifying
3x + 15 = 6x + 3
Reorder the terms:
15 + 3x = 6x + 3
Reorder the terms:
15 + 3x = 3 + 6x
Solving
15 + 3x = 3 + 6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-6x' to each side of the equation.
15 + 3x + -6x = 3 + 6x + -6x
Combine like terms: 3x + -6x = -3x
15 + -3x = 3 + 6x + -6x
Combine like terms: 6x + -6x = 0
15 + -3x = 3 + 0
15 + -3x = 3
Add '-15' to each side of the equation.
15 + -15 + -3x = 3 + -15
Combine like terms: 15 + -15 = 0
0 + -3x = 3 + -15
-3x = 3 + -15
Combine like terms: 3 + -15 = -12
-3x = -12
Divide each side by '-3'.
x = 4
Simplifying
x = 4